Positive functioning inventory: initial validation of a 12-item self-report measure of well-being - Joseph, Stephen; Maltby, John (SpringerOpen, 2014)
Background: This paper describes the validation of the Positive Functioning Inventory (PFI-12). This is a 12-item self-report tool developed to assess a spectrum of functioning ranging from states of mental distress to states of well-being. Method: Two samples (Sample 1: N = 242, mean age = 20 years. Sample 2: N = 301, mean age = 20 years) completed self-report measures of personality and social, physical and psychological functioning. Results: Evidence is provided for internal-consistency reliability, test-retest reliability, incremental validity, and convergent and discriminant validity in relation to a number of other measures of personality, social, physical and psychological functioning. Conclusion: The tool promises to be useful to practitioners and researchers who wish to assess positive psychological functioning.